TDHF Theory and Its Extensions for the Multinucleon Transfer Reaction: A Mini Review - Sekizawa, Kazuyuki (Frontiers in Physics, 2019)
Time-dependent Hartree-Fock (TDHF) theory has been a powerful tool in describing a variety of complex nuclear dynamics microscopically without empirical parameters. In this contribution, recent advances in nuclear dynamics studies employing TDHF and its extensions are briefly reviewed, in line with the study of multinucleon transfer (MNT) reactions. The latter lies at the core of this Research Topic, whose application for the production of extremely neutron-rich nuclei has been extensively discussed in recent years. Having in mind the ongoing theoretical developments, it is envisaged how microscopic theories may contribute to the future MNT study.